Asesmen Berbasis Proyek dalam Pendidikan STEM: Pendekatan untuk Mendorong Problem Solving dan Inovasi Siswa - Ningsih, Dewi Puspita; Martoni, Alfian (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2025)
This article examines the implementation of project-based assessment within STEM education (Science, Technology, Engineering, and Mathematics) and its contribution to enhancing pupils’ problem-solving abilities and innovation skills. Through the use of Project-Based Learning (PBL), pupils are engaged in contextually relevant, real-world problem-solving activities that enable them to integrate theoretical knowledge with authentic practice. The research employs a literature review approach drawing on a range of relevant sources to identify the benefits, challenges, and impacts of project-based assessment on the development of twenty-first-century competencies. The findings indicate that project-based assessment facilitates a more holistic evaluation of pupils’ abilities, encompassing cognitive, creative, collaborative, and problem-solving dimensions. This approach has also been shown to promote creativity, innovation, and cooperative work within learning groups. However, its implementation continues to face several challenges, such as difficulties in measuring individual contributions within team-based tasks and the limited availability of supporting resources in schools. The article underscores the need for strong support from educators and policymakers to address these barriers so that project-based assessment can be effectively applied in STEM education. Consequently, this assessment model holds significant potential as an effective strategy for preparing pupils to be adaptive, creative, and innovative in responding to the demands of the twenty-first century.